2006
DOI: 10.5511/plantbiotechnology.23.409
|View full text |Cite
|
Sign up to set email alerts
|

In vitro plant regeneration from the petioles of primary leaves of mungbean Vigna radiata L.

Abstract: High frequency in vitro plant regeneration via multiple shoots is reported from petioles of leaf explants of mungbean (Vigna radiata L.) on B5 culture medium supplemented with 6-benzyladenine (BA). The explants comprised of petiole cut at the node bearing the basal half of the lamina. Regeneration frequency varied with age of explant source and concentration of BA. Explants produced shoot-buds and shoots within 2 weeks. The explants harvested from 10-day-old seedlings produced higher number of shoots (8-9) tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Moreover, the appropriateness of this system toward abiotic stress resistance in leguminous plants is still unpracticed. Mung bean plants have been regenerated through, direct organogenesis by Chandra and Pal (1985), Mathew (1987), Gulati andJaiwal (1992. p. 94), Tivarekar andEapen (2001), Kumar et al (2003), Vijayan et al (2006), Mahalakshmi et al (2006), and Mundhara and Rashid (2006), and indirect organogenesis by Patel et al (1991), Mendoza et al (1992), Amutha et al (2003). However, the success of producing transgenics using these regeneration methods has been very low.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the appropriateness of this system toward abiotic stress resistance in leguminous plants is still unpracticed. Mung bean plants have been regenerated through, direct organogenesis by Chandra and Pal (1985), Mathew (1987), Gulati andJaiwal (1992. p. 94), Tivarekar andEapen (2001), Kumar et al (2003), Vijayan et al (2006), Mahalakshmi et al (2006), and Mundhara and Rashid (2006), and indirect organogenesis by Patel et al (1991), Mendoza et al (1992), Amutha et al (2003). However, the success of producing transgenics using these regeneration methods has been very low.…”
Section: Introductionmentioning
confidence: 99%
“…Only few reports are accessible on formation of transgenic plants in mung bean and all of them have employed Agrobacterium -mediated transformation (Sahoo and Jaiwal, 2008). Jaiwal et al (2001) reported recovery of transgenic plants using the nptII gene which was used as a plant selectable marker with a frequency of 0.9% whereas Mahalakshmi et al (2006) generated transgenics at a frequency of 2% using hpt gene. Sonia et al, (2007) developed transgenic plants of mung bean by transforming an insecticidal α-amylase inhibitor gene for bruchid resistance and the bar gene for herbicide resistance with a frequency of 1.15%.…”
Section: Introductionmentioning
confidence: 99%